Two emissaries of General José de San Martín in Peru: Remigio Silva and Fernando López Aldana - Peralta Ruiz, Víctor (2021)
This article rescues two characters from historiographical oblivion: Remigio Silva from Lima and Fernando López Aldana from Bogotá. In different contexts, both assumed key roles as emissaries of General José de San Martín before his landing in Peru. Silva played a relevant role in the success of Lord Cochrane’s naval expedition, while López Aldana was a popularizer of San Martín propaganda in Lima. The prominence of Silva and López Aldana was key in the “undercover war” within the viceroyalty that simultaneously connected Rio de la Plata, Chileans and Peruvians.